Determination of some heavy metal levels in soft drinks from Turkey using ICP/OES method - Mehmet Bingöl; Gülderen Yentür; Buket Er; Aysel Bayhan Öktem (Czech Journal of Food Sciences, 2010)
Total number of 104 canned soft drinks collected from several regions in Turkey were analysed. The purpose of this study was to determine the levels of heavy metals in the drinks commonly consumed in Turkey. Quantitative determination of heavy metals: arsenic, copper, zinc, cadmium, and lead in all samples was carried out by ICP-OES (Inductively Coupled Plasma-Optical Emission Spectrometry) method. The mean levels (± SE) of arsenic, copper, zinc, cadmium, and lead were found to be 0.037 ± 0.002 mg/kg, 0.070 ± 0.009 mg/kg, 0.143 ± 0.012 mg/kg, 0.005 ± 0.0003 mg/kg, and 0.029 ± 0.002 mg/kg, respectively, in soft drinks. Our data revealed that arsenic, copper, zinc, cadmium, and lead mean levels found in all soft drinks, collected from several regions in Turkey, were within the Turkish Food Codex (TFC) values.